1992
DOI: 10.1161/01.atv.12.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins and their genetic variation in subjects with and without angiographically verified coronary artery disease.

Abstract: To examine the concentration of serum lipoproteins and the association of their genetic variation with the occurrence of coronary artery disease (CAD), composite serum lipoprotein profiles including lipoprotein(a) (Lp[a]), apolipoprotein (apo) E phenotypes, and apo BXba I genotypes were determined in patients with angiographically verified CAD (CAD+ group, n = l l l ) and in subjects with no angiographic evidence of CAD (CAD-group, n=46). In addition, we determined the concentrations of serum lipids, lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 81 publications
6
25
1
Order By: Relevance
“…However, this linkage may not be present in all populations, since our previous study showed only an insignificantly higher frequency of the XI allele in Finnish patients with angiographically confirmed coronary constrictions compared with patients with other cardiac diseases but no angiographic evidence of atherosclerosis (61% versus 54%). 35 The higher frequency of the apoC-III 52 allele among the centenarians than among the younger Finns (Table 2) was a somewhat unexpected finding. We have previously detected the 52 allele in approximately 60% of Finnish patients with severe primary hypertriglyceridemia but in only 16% (P<.001) of healthy normolipidemic subjects.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this linkage may not be present in all populations, since our previous study showed only an insignificantly higher frequency of the XI allele in Finnish patients with angiographically confirmed coronary constrictions compared with patients with other cardiac diseases but no angiographic evidence of atherosclerosis (61% versus 54%). 35 The higher frequency of the apoC-III 52 allele among the centenarians than among the younger Finns (Table 2) was a somewhat unexpected finding. We have previously detected the 52 allele in approximately 60% of Finnish patients with severe primary hypertriglyceridemia but in only 16% (P<.001) of healthy normolipidemic subjects.…”
Section: Discussionmentioning
confidence: 90%
“…Although the following is not true of all populations examined, 5 ' 6 in Finland the apoE phenotype E4 has been associated with an elevated serum LDL cholesterol level 8 and is known to be more common among patients with angiographically confirmed coronary disease than in the general population 15 or in patients with cardiac disease who have normal coronary angiograms. 35 In addition, the apoE e4 allele may promote accelerated atherosclerosis by mechanisms other than that operating via increased serum LDL cholesterol levels, 3638 and some of these mechanisms may be important for life expectancy. Our data confirm the results of Davignon et al 22 and Eggertsen et al, 23 who both were able to show a decrease of the e4 allele frequency in elderly people compared with younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bohn and Berg (17) cited significant positive associations between CAD and the Xallele and/or the X-X-genotype in five studies (6-10), and reported that this association was not observed in seven other studies (18)(19)(20)(21)(22)(23)(24). The X-X-genotype was more frequent in Brazilian women with CAD than in control women (25).…”
Section: Discussionmentioning
confidence: 99%
“…Strong associations between the frequency of CAD, ischemic heart disease (IHD), or CHD and the frequency of the ApoE genotypes carrying the ⑀4 allele have been found in case control studies, 18 -21,44 -46 in studies of special population subgroups, 16,17,47 and recently in a prospective study. 22 These results have raised expectations that the ApoE polymorphism may be useful in identifying asymptomatic individuals who are at higher risk of CAD.…”
Section: Association Of Cad With Apoe Genotypementioning
confidence: 99%